2003
DOI: 10.1038/sj.leu.2403068
|View full text |Cite
|
Sign up to set email alerts
|

Response to imatinib in patients who relapse after allogeneic stem cell transplantation for chronic myeloid leukemia

Abstract: We studied 128 patients with chronic myeloid leukemia (CML) relapsing after allogeneic stem cell transplantation (SCT). Disease at the time of treatment with Imatinib was in chronic phase (CP) in 51 patients, accelerated phase (AP) in 31 and blastic crisis (BC) in 46. Of the 51 patients in CP, 14 were in cytogenetic and two in molecular relapses. The median interval between relapse and Imatinib therapy was 5 months (0-65). A total of 50 patients had failed treatment with donor lymphocyte infusions prior to Ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 21 publications
2
76
3
5
Order By: Relevance
“…These results seem to be comparable to those obtained in CP patients and better than those reported in AP patients with DLI as first-line treatment. 10,11,13,15 Incidence of severe GvHD and marrow suppression after imatinib was low in this study; however, other authors have recently reported recurrence of GvHD and severe trombocytopenia and granulocytopenia in up to 40% of patients treated with imatinib. 14 The efficacy of imatinib must be compared with DLI, which has a response rate of 64-86%, associates severe GvHD in 50% of patients, and marrow aplasia in up to 25% of patients with hematological relapses.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…These results seem to be comparable to those obtained in CP patients and better than those reported in AP patients with DLI as first-line treatment. 10,11,13,15 Incidence of severe GvHD and marrow suppression after imatinib was low in this study; however, other authors have recently reported recurrence of GvHD and severe trombocytopenia and granulocytopenia in up to 40% of patients treated with imatinib. 14 The efficacy of imatinib must be compared with DLI, which has a response rate of 64-86%, associates severe GvHD in 50% of patients, and marrow aplasia in up to 25% of patients with hematological relapses.…”
Section: Discussioncontrasting
confidence: 39%
“…In this sense, a retrospective EBMT study has shown the results of treating with imatinib a total of 128 patients relapsing in different phases of the disease (51 CP, 31 AP, and 46 BC). 13 A total of 50 patients had failed treatment with DLI prior to imatinib. The complete cytogenetic response was 58% for patients in CP, 48% for AP, and 22% for patients in BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imatinib mesylate has been widely used to restore remission in patients relapsing after allogeneic SCT. [12][13][14] These series have reported patients with predominantly haematologicalal relapse post allogeneic SCT, some of whom also received DLI either prior to or concurrently with imatinib. Kantarjian et al 12 reported a series of 28 patients who achieved a complete haematological response rate of 74% and cytogenetic response rate of 58%, with CCR in 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Outros foram tratados em recidiva citogenética ou hematológica, frequentemente na presença de imunossupressão para o tratamento da DECH e/ou falência da ILD. [81][82][83][84][85] O EBMT reportou uma análise retrospectiva de 128 pacientes tratados com IM para recidiva após um TCTH. 80 A resposta hematológica global foi de 84% (98% para os pacientes em FC).…”
Section: Tratamento Da Recidivaunclassified